Chromaticity-Adaptive Generalized Spatial Modulation for MIMO VLC With Multi-Color LEDs - Ye Xiao; Yi-Jun Zhu (IEEE Photonics Journal)
In this paper, we propose a chromaticity-adaptive generalized spatial modulation (CA-GSM) method for multiple-input multiple-output (MIMO) visible light communication (VLC) systems with quadrichromatic LEDs (QLEDs). After the MIMO-VLC system model is constructed, the CA-GSM method based on chromaticity-adaptive constellation optimization is brought forward accounting for the correlated MIMO channel with multi-color crosstalk and quadrangle chromaticity region. This work mainly investigates the optimal active QLED selection pattern in CA-GSM aiming at maximizing the minimum Euclidean distance of received multi-color constellation. Considering power, amplitude and chromaticity constraints, the optimization problem of chromaticity-adaptive constellation is transformed and solved by the linear approximation of Taylor series. Therefore, the design algorithm of CA-GSM is derived with the optimal QLED selection pattern. Simulation results verify that our proposed CA-GSM can achieve performance improvement compared to the multi-stream spatial modulation and the conventional design method without considering channel.